EXPERIMENTAL STUDY ON SOME CHARACTERISTICS OF DENTAL RESTORATION FILLINGS USED IN CORONARY THERAPEUTIC MANAGEMENT OF FIRST PERMANENT MOLAR - Veronica Pintiliciuc Şerban; Eugen Mihalaş; Eduard Radu Ciornei; Adriana Bălan (Romanian Society of Oral Rehabilitation, 2015)
Introduction Many modern materials used by modern medicine are in close contact or interact with tissues or body fluids, therefore their selection must take into consideration not only the physical and long-term stability but also biological compatibility. Modern coronal restorative materials such as composites, glass ionomer cements and compomers have many of the characteristics of bioactive materials. The interface of such material and dental hard tissues involves not only extremely close physical contact but also the establishment of chemical bonds. This is why biocompatibility of modern materials to tissue subjacent and in particular to the pulp organ is of the most importance. Aim of the study The aim of our study is to determine how the physicochemical characteristics of modern restorative materials are passed on to their clinical and functional characteristics. Material and methods In compression tests were tested the following restorative materials : (1) universal hybrid light-cured composite Charisma; (2) ( Composite Curing consistency controlled fluid Flow - line.those materials were applied according to the manufacturer to recent extracted teeth that were maintained in the physiological saline until processed.After the application of restoration, the root of the tooth crowns were sectioned and included in the epoxy resin in the tubes 8 mm height and 12 mm diameter. Before introduction into the liquid media, surface of samples were processed, maintaining constantly the hydration of the tooth, on abrasive paper with different grain sizes, till we achieved a planar surface. Compression test was carried out with a specific installation provided with the equipment computer-aided acquisition of experimental data. The research was conducted in the Department of Unconventional Technologies of the Polytechnic Institute of Iasi, following the resistance of material compression. Results and discussion Statistical analysis of experimental data relating to the values of the compressive strength, in experimental conditions used for the compressions tests, have not shown a significant difference between the mean values. However, we observed a higher value of compressive strength for the composite flow, which is consistent with the microhardness measurements. Tougher materials are brittle and tend to crack more. Although compressive strength values not significantly different from the corresponding experiments, a slight difference is observed values, however, from the literature data they are still different.The results of the statistical analysis shows that to achieve the best results, the materials must be prepared according to the manufacturer, otherwise there is a chance that sustainability fillings to become highly reduced. Conclusions As expected, the studies carried out have shown that the properties of the dental materials studied are dependent on the nature of the investigation, of the chemical composition and of the method of preparation used. Compressive strength of the composites differ, a greater value being obtained for the composite flow. The durability of dental restorations, judged by wear resistance, which is measured by the amount of material microhardness is higher for light-cured composite restorations than composite flow.